Regulatory T cells targeting a pathogenic MHC class II: Insulin peptide epitope postpone spontaneous autoimmune diabetes - Obarorakpor, Nyerhovwo; Patel, Deep; Boyarov, Reni; Amarsaikhan, Nansalmaa; Cepeda, Joseph Ray; Eastes, Doreen; Robertson, Sylvia; Johnson, Travis; Yang, Kai; Tang, Qizhi; Zhang, Li (Frontiers in Immunology, 2023)
In spontaneous type 1 diabetes (T1D) non-obese diabetic (NOD) mice, the insulin B chain peptide 9-23 (B:9-23) can bind to the MHC class II molecule (IA g7 ) in register 3 (R3), creating a bimolecular IA g7 /InsulinB:9-23 register 3 conformational epitope (InsB:R3). Previously, we showed that the InsB:R3-specific chimeric antigen receptor (CAR), constructed using an InsB:R3-monoclonal antibody, could guide CAR-expressing CD8 T cells to migrate to the islets and pancreatic lymph nodes. Regulatory T cells (Tregs) specific for an islet antigen can broadly suppress various pathogenic immune cells in the islets and effectively halt the progression of islet destruction. Therefore, we hypothesized that InsB:R3 specific Tregs would suppress autoimmune reactivity in islets and efficiently protect against T1D. To test our hypothesis, we produced InsB:R3-Tregs and tested their disease-protective effects in spontaneous T1D NOD. CD28 -/-mice. InsB:R3-CAR expressing Tregs secrete IL-10 dominated cytokines upon engagement with InsB:R3 antigens. A single infusion of InsB:R3 Tregs delayed the onset of T1D in 95% of treated mice, with 35% maintaining euglycemia for two healthy lifespans, while whereas control Tregs did not. Our data demonstrate that Tregs specific for MHC class II: Insulin peptide epitope (MHCII/Insulin) protect mice against T1D more efficiently than polyclonal Tregs lacking islet antigen specificity, suggesting 2 This is a provisional file, not the final typeset article that the MHC II/insulin-specific Treg approach is a promising immune therapy for safely preventing T1D.